Transformasi Karakter Melalui Pendidikan Islam: Menanamkan Nilai-Nilai Moral dan Etika di Era Modern Di SMPIT Darussalam Sangatta - Putri Zarifah; Faelasup Faelasup (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Islamic education plays a crucial role in character building by instilling moral and ethical values. In the modern era, characterized by the challenges of globalization, technological advancements, and rapid social changes, the need for education that can foster strong moral character is increasingly urgent. This article examines the role of Islamic education in character transformation, focusing on how the moral and ethical values taught in Islamic education can be applied in daily life. Through a comprehensive approach encompassing formal education in Islamic schools and informal education through family and community, Islamic education strives to instill values such as honesty, responsibility, respect, and compassion. Additionally, Islamic education emphasizes the importance of a spiritual relationship with Allah as a strong moral foundation. By integrating religious teachings and daily practices, individuals are expected to internalize these values and make them part of their personal character. This study employs a qualitative method with a case study approach to delve deeper into how Islamic education influences character transformation among students. Data were collected through in-depth interviews, participatory observation, and analysis of relevant documents. The findings indicate that students receiving Islamic education tend to have a better understanding of moral and ethical values and are able to apply them in their social interactions. However, challenges such as resource limitations, curriculum mismatches, and the negative influence of social media were also identified as obstacles in the character education process. In conclusion, Islamic education has significant potential in shaping individuals with strong moral and ethical character. With consistent value inculcation and support from a conducive environment, Islamic education can be key in addressing moral challenges in the modern era